Evaluating Strategic Human Recourse Management’s Influence on Employee Productivity in Bangladesh’s NGO - Dash, Partho Sarothi (The Institute of Academic Research and Publication (IARP), 2024)
Strategic human resource management techniques involve a strong emphasis on recognizing the value of each individual inside the firm to ensure employees are committed to its long-term objective. The goal of the study is to determine how strategic HRM factors affect employee productivity in Bangladesh's NGOs from the perspective of the NGO managers. From various organizations of NGOs in Bangladesh, a total of 50 different categories of employees were chosen. Analysis reveals that in NGOs, strategic HRM significantly affects Employee productivity. The executive authority and HR department of NGO should be aware of and concerned with addressing these strategic issues on employee productivity which will ultimately utilize the implementation costs of Strategic human resource management (SHRM). Further study can be evaluated other sectors of Bangladesh.